2010
DOI: 10.2115/fiber.66.215
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid-assisted Electroless Copper Plating of Aramid Film:The Influence of Surface Treatment

Abstract: For over 50 years, plastic materials have been replacing metals in many different fields (automobiles, housing, safety and computers). Indeed, polymers are more versatile and can thus be modeled to exactly fit their new specific usages such as intelligent fibers or nano fibers. However, until recently, scientists faced the problem of the non-conductivity of polymers. Hence, they developed various metallization processes 1-3 to create smaller and lighter electrical devices. With the realization that industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Moreover, the poly(dopamine) layer could be used as a versatile platform for secondary reactions and improve the wettability of the hydrophobic materials. The metal-binding ability brought about by the catechols present in the poly(dopamine) (PDA) coating made it possible to deposit adherent and uniform metal coatings onto the substrates by electroless plating without conventional processes such as coarsening, sensitizing, and activating, which are cumbersome and toxic. , However, to the best of our knowledge, the fabrication of surface silvered polymetaphenylene isophthamide (PMIA) via dopamine functionalization is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the poly(dopamine) layer could be used as a versatile platform for secondary reactions and improve the wettability of the hydrophobic materials. The metal-binding ability brought about by the catechols present in the poly(dopamine) (PDA) coating made it possible to deposit adherent and uniform metal coatings onto the substrates by electroless plating without conventional processes such as coarsening, sensitizing, and activating, which are cumbersome and toxic. , However, to the best of our knowledge, the fabrication of surface silvered polymetaphenylene isophthamide (PMIA) via dopamine functionalization is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…16 Zhao et al 17 designed a new pretreatment process, in which the organometallic complex was impregnated into Kevlar® fabrics/bers by using ScCO 2 to electro conductive composite fabrics/bers and metalizing aramid bers using supercritical by copper plating of aramid lm. 18 In an early study, we have reported a new method by inltrating polymeric materials into aramid lament networks to improve their mechanical properties with the aid of ScCO 2 . 19 In this study, the surface and the adhesion properties of aramid bers were further researched.…”
Section: Introductionmentioning
confidence: 99%
“…Polycarbonate has been impregnated with silver nitrate in scCO 2 , resulting up to 99.9% bacteria reduction [53]. Belmas and co-workers [54][55][56] have used scCO 2 process to impregnate a range of organometallic complexes in a synthetic polymer prior to electroless copper plating to improve the adhesion of copper to the polymer. The adhesion between the copper and polymer was much improved after scCO 2 impregnation of the organometallic complexes.…”
Section: Organometallic-based Functional Agentsmentioning
confidence: 99%